2021
DOI: 10.3390/nano11123198
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of SAPO-34 Nanoplates with High Si/Al Ratio and Improved Acid Site Density

Abstract: Two-dimensional SAPO-34 molecular sieves were synthesized by microwave hydrothermal process. The concentrations of structure directing agent (SDA), phosphoric acid, and silicon in the gel solution were varied and their effect on phase, shape, and composition of synthesized particles was studied. The synthesized particles were characterized by various techniques using SEM, XRD, BET, EDX, and NH3-TPD. Various morphologies of particles including isotropic, hyper rectangle, and nanoplates were obtained. It was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…There were significantly more acid sites observed on the 5Ni+1Sr/SAPO-5 catalyst (1.65 mmol/g) than on the 5Ni/SAPO-5 catalyst (1.03 mmol/g). It shows that a broad range of acid strengths were exhibited by all of the catalysts that were generated [44]. It was observed that the catalysts 5Ni+1Ce/SAPO-5 and 5Ni+1Cu/SAPO-5 only showed a single peak at about 300 • C, but the supported catalysts, 5Ni +1Sr/SAPO-5, had two peaks at 300 • C and 480 • C [45,46].…”
Section: Temperature-programmed Desorption (Nh 3 -Tpd)mentioning
confidence: 96%
“…There were significantly more acid sites observed on the 5Ni+1Sr/SAPO-5 catalyst (1.65 mmol/g) than on the 5Ni/SAPO-5 catalyst (1.03 mmol/g). It shows that a broad range of acid strengths were exhibited by all of the catalysts that were generated [44]. It was observed that the catalysts 5Ni+1Ce/SAPO-5 and 5Ni+1Cu/SAPO-5 only showed a single peak at about 300 • C, but the supported catalysts, 5Ni +1Sr/SAPO-5, had two peaks at 300 • C and 480 • C [45,46].…”
Section: Temperature-programmed Desorption (Nh 3 -Tpd)mentioning
confidence: 96%
“…The obtainment and application of nanomaterials in the form of the film have found excellent uses of great technological utility [ 8 , 9 , 10 ], even reaching the needs of aerospace and advanced manufacturing technology [ 11 ].…”
mentioning
confidence: 99%